Pentingnya Pemahaman E-Commerce Bagi Masyarakat di Era Digital - Fiqkri Ardian; Zuhrinal M. Nawawi (Economic Reviews Journal, 2022)
In this digital era, the internet can be used as a medium for education, health, government and entrepreneurship which will make it easier for someone to do things electronically.The Internet now teaches how to do business, from small businesses to large businesses. By using the internet as a business platform for the community to benefitThe Internet now teaches how to do business, from small businesses to large businesses. By using the internet as a business platform for the community to benefit optimal. This can be seen from the increase in online shopping statistics for the world community. This study will explain how much opportunity the Indonesian people have in using the internet as a source of informationoptimal. This can be seen from the increase in online shopping statistics for the world community. This study will explain how much opportunity the Indonesian people have in using the internet as a source of information business media. Keywords: Internet, business, e-commerce, entrepreneurship.